Black widows - Murray, Peter ([Mankato, MN] : Child's World ; Chicago, Ill. : Distributed to schools and libraries in the U.S. by Encyclopedia Britannica Educational Corp., 1992)
Introduces the physical characteristics and behavior of the black widow spider.
Keywords: Black widow spider; Black widow spider; Spiders